2014
DOI: 10.1002/ange.201405566
|View full text |Cite
|
Sign up to set email alerts
|

Misfolding of Luciferase at the Single‐Molecule Level

Abstract: The folding of complex proteins can be dramatically affected by misfolding transitions. Directly observing misfolding and distinguishing it from aggregation is challenging. Experiments with optical tweezers revealed transitions between the folded states of a single protein in the absence of mechanical tension. Nonfolded chains of the multidomain protein luciferase folded within seconds to different partially folded states, one of which was stable over several minutes and was more resistant to forced unfolding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…Interactions of the nascent polypeptide with the ribosome are beneficial for folding soon (but not immediately) after the domain has been synthesized (Figure 1). Experiments with full-length EF-G (Liu et al, 2017) and other multi-domain proteins (Jahn et al, 2016;Mashaghi et al, 2014;Scholl et al, 2017) have previously suggested misfolding among domains. Here, we directly observe misfolding among EF-G domains (Figure 2) and further demonstrate that a natively structured N-terminal G-domain is a prerequisite for stable folding of the subsequently synthesized domain II (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Interactions of the nascent polypeptide with the ribosome are beneficial for folding soon (but not immediately) after the domain has been synthesized (Figure 1). Experiments with full-length EF-G (Liu et al, 2017) and other multi-domain proteins (Jahn et al, 2016;Mashaghi et al, 2014;Scholl et al, 2017) have previously suggested misfolding among domains. Here, we directly observe misfolding among EF-G domains (Figure 2) and further demonstrate that a natively structured N-terminal G-domain is a prerequisite for stable folding of the subsequently synthesized domain II (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…For example, dimeric prion protein was found to misfold into a stable aggregated state via multiple intermediates, with much slower diffusion than for native folding indicating a rougher energy landscape for misfolding [27 ]. The slow refolding of the enzyme luciferase and its propensity to aggregate were linked to the formation of a misfolded state [47]. The effects of calcium concentration on misfolding of a calcium sensor, neuronal calcium sensor-1 (NCS-1) [48 ] suggested the missing link between Ca 2+ dysregulation, misfolding, and a NCS protein involved in neurodegenerative disorders [49,50].…”
Section: Probing Interactions That Influence Protein Misfolding and Amentioning
confidence: 99%
“…NanoLuc is a 19.1 kDa enzyme that catalyzes the conversion of furimazine to furimamide, a process that emits visible light that can be detected [ 78 ]. While there have been a few SMFS studies on bioluminescent proteins including Firefly Luciferase (FLuc) in the past [ 53 , 67 , 79 ], FLuc bioluminescence is likely too weak to be registered at a single molecule level using current detection technologies; NanoLuc is able to emit 150× more light compared to FLuc [ 78 , 80 ]. We expect that unraveling of the tertiary structure of NanoLuc due to mechanical unfolding should be accompanied by a significant decrease in its bioluminescence activity.…”
Section: Introductionmentioning
confidence: 99%